Clock gene affect the noncanonical NF-κB pathway via circadian variation of Otud7b. Issue 6 (2nd November 2017) - Hou, Wang; Jiang, Zhou; Ying, Junjie; Ding, Lu; Li, Xiaoxue; Qi, Fang; Yang, Shuhong; Cheng, Shuting; Wang, Yuhui; Liu, Yanyou; Xiao, Jing; Guo, Huiling; et al.
Abstract: The circadian system regulates many important aspects of physiology, including the immune response to infectious agents, which is mediated by the activation of the transcription factor NF-κB. Thus, understanding the mechanisms by which circadian clocks regulate NF-κB is a necessary step toward the development of improved therapies underwritten by NF-κB manipulation. Previous reports have identified OTUD7B a deubiquitinase, as a novel regulator of noncanonical NF-κB signaling, largely through the maintenance of TRAF3, a negative regulator of NF-κB. In investigations in our laboratory, when the Clock gene was repressed by shRNA, the results of microarray analysis demonstrated that Otud7b was down-regulated. Further research by real-time PCR and western blot revealed that that Otud7b exhibits rhythmic mRNA expression. These findings confirm Otud7b as a novel clock -regulated gene. Additionally, Otud7b may be an important bridge between the circadian system and noncanonical NF-κB pathway regulation.